2018
DOI: 10.1302/0301-620x.100b7.bjj-2017-1590.r2
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic prosthesis surfaces induce an inflammatory cell response and fibrotic tissue changes

Abstract: Our findings therefore, corroborate the previous findings that ceramic-on-ceramic periprosthetic revision tissue is fibrous and offer an explanation for this observation. We detected a long-term inflammatory response of PBMCs and an inflammatory response of fibroblasts to ATZ and ZTA ceramic. These findings partially explain the fibrotic tissue change in periprosthetic tissue of ceramic-on-ceramic bearings. Cite this article: Bone Joint J 2018;100-B:882-90.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The previously reported incidence of ceramic fracture after C-O-C THA varied between 0.26% and 13.4% [34], whereas that of squeaking ranged from 0% to 10.7% [34]. In (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) .961 Vertical (mm)…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The previously reported incidence of ceramic fracture after C-O-C THA varied between 0.26% and 13.4% [34], whereas that of squeaking ranged from 0% to 10.7% [34]. In (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) .961 Vertical (mm)…”
Section: Discussionmentioning
confidence: 96%
“…Ceramic hip implants have generally been considered to be inert, and they do not produce osteolysis caused by wear particles [17]. Rony et al [46] and Bertand et al [47], however, described that the generation of wear particles from C-O-C articulations may be biologically active. Bertrand et al [47] found that the fibrotic response was more pronounced in C-O-C bearings compared with the tissues obtained from metal-on-metal or ceramic-onpolyethylene pairings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ample evidence is available for the pathological role of polyethylene particles in the mechanisms leading to PPOL and AL [11,[29][30][31][32]. Biotribological experiments demonstrate that even hard materials like ceramics generate nano-sized debris that could induce inflammation [33].…”
Section: Stimuli Of Periprosthetic Inflammationmentioning
confidence: 99%
“…Joints perform tens of thousands of frictional movements in their lifetime [ 4 ]. Although the wear rate of alumina ceramic has been shown to be less than 1 μm/year, the fine particles (FPs) of Al 2 O 3 are generated by continuous frictional movement, which may promote inflammation in the adjacent tissue of implant [ 2 , 3 , 5 , 6 ]. Previous studies have shown that the treatment of Al 2 O 3 FPs induced activation of human macrophages, which produced higher levels of tumor necrosis factor-α (TNF-α) [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%